The Routledge history of the modern maritime world since 1500
1 online resource (xix, 549 pages)
Keywords: "The Routledge History of the Modern Maritime World provides a wide-ranging set of chapters, covering the sixteenth century to the present, which represent the main lines of current enquiry in maritime history. Over the past half-century, maritime history has become a significant sub-field of historical research that intersects with broader historical concerns such as oceanic history, global patterns of production and consumption, and the maritime heritage industry. Informed by original research, an engagement with current historiographical concerns, and a global geographical reach, the book is divided into sections covering shipping, ports, merchants and trade, maritime environments, coastal zones, and the human dimension. Chapters focus on different countries, across different ranges of time, and also with different methodological approaches. The six sections that the book is divided into, show the significant areas central to the study and understanding of the modern maritime world and collectively, they highlight the areas in which the themes pursued by maritime historians have advanced and are currently moving. This book will appeal to various academic audiences; students will find chapters dealing with major topics in maritime history that will help them in their courses, for professional scholars in history, archaeology, heritage studies, historical sociology and economics chapter outline some of the latest research in the field"-- Provided by publisher.